Selection of the optimal real estate investment project basing on multiple criteria evaluation using stochastic dimensions - Ginevičius, Romualdas; Zubrecovas, Viktoras (Journal of Business Economics and Management, 2009)
As investment in real estate has great influence on regional economics development it is important to evaluate real estate investment processes as a whole. For this purpose the model of real estate projects’ efficiency evaluation was developed and presented in this article. The proposed model is designed for alternative projects, variants selection, investment resources allocation as well as real estate value maintenance and enhancement problems solution. The model of real estate projects’ efficiency evaluation covers all the investment decision‐making cycle, the hierarchically‐structured projects’ evaluation criteria system, risk evaluation basing on stochastic dimensions as well as the mathematical methods adaptation for multiple criteria evaluation problems solution, risk assessment and adjusted mathematical methods is presented in this issue. First Publish Online: 14 Oct 2010